EL SINÚ Y LAS SABANAS - Montes Mathieu, Roberto; Martínez Simanca, Albio (Cuadernos de Literatura del Caribe e Hispanoamérica, 2008)
El texto contiene un panorama acerca de la ubicación geográfica, social, económica y cultural de la región del Sinú y las Sabanas, en los departamentos de Córdoba y Sucre, al norte de Colombia. Explica los orígenes de la literatura de la región a partir de la llegada de la imprenta, la aparición de los primeros periódicos, las tertulias, y los centros educativos, como antesala de los escritores que surgirían en la época contemporánea. PALABRAS CLAVES Geografía, región, cultura, literatura, periodismo, imprenta, libros, escritores. ABSTRACT This text presents an overview of the geographical, social, economic and cultural location of the Sinú and Las Sabanas region in Córdoba and Sucre in the north part of Colombia. It explains the origins of the literature of this region, beginning with the arrival of the printing machine, the upcoming of the first newspapers, the literary discussions and the educational centers, all of these seen as events that occurred prior to the appearance of those writers that would emerge in the contemporary epoch. KEY WORDS Geography, region, culture, literature, journalism, printing machine, books, writers.